2015
DOI: 10.1002/2015ms000495
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of an intraseasonal oscillation in an aquaplanet general circulation model

Abstract: MJO initiation is studied in an aquaplanet general circulation model that has strong and highly regular MJO-like variability. About 80% of MJO events in the model are found to be successive events, immediately preceded by another strong MJO event. Hence, the dynamics of MJO initiation in the model are dominated by interactions with preceding events. Rossby gyres associated with the previous cycle of suppressed MJO convection to the east are shown to help initiate the next cycle of MJO convection in the western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 69 publications
(142 reference statements)
8
18
0
Order By: Relevance
“…The anticyclonic Rossby gyres forced by large‐scale suppressed convection are located in 110 °E–160 °E (as seen in Figure ). Referring also to individual contributions of zonal and meridional wind components to horizontal advection (Figures c and d), we found that the meridional advection related to Rossby gyres dominates the moistening in region A, as reported by Zhao et al () and Maloney and Wolding (). Meanwhile, the moistening in region B seems to be associated with another process.…”
Section: Initiation Processes Of Composite Mjo‐like Disturbances In Tsupporting
confidence: 86%
See 3 more Smart Citations
“…The anticyclonic Rossby gyres forced by large‐scale suppressed convection are located in 110 °E–160 °E (as seen in Figure ). Referring also to individual contributions of zonal and meridional wind components to horizontal advection (Figures c and d), we found that the meridional advection related to Rossby gyres dominates the moistening in region A, as reported by Zhao et al () and Maloney and Wolding (). Meanwhile, the moistening in region B seems to be associated with another process.…”
Section: Initiation Processes Of Composite Mjo‐like Disturbances In Tsupporting
confidence: 86%
“…In addition, the east‐west ratio of the spectral power for 15 °S–15 °N OLR filtered for zonal wavenumbers 1–4 and periods of 20–100 days is 1.82. These imply that the absence of circumnavigation of Kelvin waves is irrelevant to the existence of MJO‐like disturbances, consistent with Zhao et al (), Maloney and Wolding (), and Ma and Kuang (). However, the frequency at the spectral peak associated with MJO‐like disturbances was lower in the KDAMP experiment (more than 50 days), which suggests that it takes longer for large‐scale deep convective activities to initiate without circumnavigating Kelvin waves.…”
Section: Sensitivity Experimentssupporting
confidence: 85%
See 2 more Smart Citations
“…The impact of this rectified heating on large-scale subsidence-and hence on the onset process-is captured through the WTG framework. In nature, equatorial waves can also influence the onset process [Maloney, 2009;Powell and Houze, 2015;Maloney and Wolding, 2015]; this study's focus is limited to the influences of local diabatic processes, however. The experimental methodology is described next, with results in section 3, and summary and conclusions in section 4. lowest 2 km), smoothly stretched to Dz 5 350 m for z > 15 km.…”
Section: Introductionmentioning
confidence: 99%